Between Sinology and Socialism: Collective Memory of Czech Sinologists in the 1950s - Cheng, Ter-Hsing (Mongolian Journal of International Affairs, 2015)
This paper intends to explore the collective memory of Czech sinologists in the 1950s based on the political zone between sinology and socialism. Czech sinological development in the 1950s was grounded on the personal factor of Prusek and the socialist transformation of new China. Socialist China offers two possibilities for the development of sinology, the first for friendly relations among socialist countries, including overseas students, and the second for studies of contemporary Chinese literature. The developmental framework of Czech sinology in the 1950s, or the social framework of collective memory for the Czech sinologists should be understood in the region under the mutual penetration of sinology and socialist China. This paper, firstly, discusses the background framework of constructing the Czech sinologists in the 1950s— the link between new China and the other socialist countries, and the relation between Prusek and socialist China. Secondly, this paper will analyze Czech sinological experiences in the 1950s through Halbwachs’ theory of collective memory. Mongolian Journal of International Affairs Vol.19 2014: 116-133